High-frequency electrical stimulation of cutaneous nociceptors differentially affects pain perception elicited by homotopic and heterotopic electrical stimuli - van den Broeke, Emanuel N. (2021)
Animal studies have shown that high-frequency electrical stimulation (HFS) of peripheral C-fiber nociceptors induces both homosynaptic and heterosynaptic long-term potentiation (LTP) within spinal nociceptive pathways. In humans, when HFS is applied onto the skin to activate nociceptors, single electrical stimuli are perceived more intense at the HFS site compared with a control site, a finding that was interpreted as a perceptual correlate of homosynaptic LTP. The present study aimed to investigate if after HFS the pain elicited by electrical stimuli delivered at the skin next to the HFS site is perceived as more intense compared with the pain at a control site (contralateral arm). To test this, HFS was applied to one of the two ventral forearms of 24 healthy participants. Before and after HFS, single electrical stimuli were delivered through the HFS electrode, through an identical electrode next to the HFS electrode and an identical electrode at the contralateral arm. After HFS, the pain elicited by the single electrical stimuli was reduced at all three sites, with the largest reduction at the HFS site. Nevertheless, electrical stimuli delivered to the skin next to the HFS site were perceived as more intense than control stimuli. This result indicates that higher pain ratings to electrical stimuli after HFS at the HFS site cannot solely be interpreted as a perceptual correlate of homosynaptic changes. Furthermore, we show for the first time, in humans, that HFS can reduce pain elicited by single electrical stimuli delivered through the same electrode.